Delay in cardiology consultation after primary care physician referrals in heart failure: Clinical implications - Sergio Cinza‐Sanjurjo; Alberto Cordero; Pilar Mazón‐Ramos; Daniel Rey‐Aldana; Oscar Otero García; Ines Gómez‐Otero; Manuel Portela Romero; David Garcia‐Vega; José R. González‐Juanatey (ESC Heart Failure)
Abstract Aims To investigate the association between the elapsed time to cardiology care following a primary care physician (PCP) referral and 1 year outcomes among patients with heart failure (HF). Methods Data from electronic medical records at our institution encompassing all PCP referrals to cardiology consultation from 2010 to 2021 (N = 68 518) were analysed. Of these, 6379 patients had a prior diagnosis of HF. Using a Cox regression model for hospitalization and mortality outcomes, the association between delay time in cardiology care post‐PCP referral and 1 year outcomes was examined, adjusting for age, gender and comorbidities. Results A significant increase in 1 year mortality rates with delayed cardiology care was observed for each day: all‐cause (0.25%), cardiovascular (CV) (0.13%) and HF (0.11%). In multivariate analysis, continuous delay to consultation was independently associated with higher risk of all‐cause [hazard ratio (HR): 1.02; 95% confidence interval (CI) (1.01–1.02); P < 0.01], CV [1.01 (1.00–1.02); P < 0.01] and HF mortality (HR: 1.01; 95% CI 1.00–1.03; P < 0.01). Patients attended in the 25th quartile of time delay (<2 days) had significantly lower mortality and HF readmission rates [1.21 (1.10–1.33); P < 0.01] as compared with patients in the 75th quartile (>14 days). Conclusions Delay in cardiology assistance following a PCP referral among patients previously diagnosed with HF was associated with increased in all‐cause, CV, and HF mortality at 1 year.